Organometallic & Bioinorganic Chemistry - Kumar, Ajai (Muzaffarnagar: Aaryush Education, 2023)
The content given in the book will be invaluable to teaching and learning concept of Organometallic & Bioinorganic Chemistry. The questions, objective and subjective have the levels of various competition exams like IIT-JAM, CSIR-UGC (JRF/NET), GATE, IISC, BARC, TIFR, DRDO, ONGC, NTPC, NBRC etc. The fundamentals of Organometallic & Bioinorganic Chemistry are written according to the need of the students.
Includes index
Keywords: Organometallic compounds; Bioinorganic chemistry; Inorganic chemistry